Pelatihan Pembuatan Asesmen Formatif Berbasis Educaplay Bagi Guru MGMP Sejarah Kabupaten Barito Kuala Kalimantan Selatan - Sriwati; Melisa Prawitasari; Fitri Mardiani; Octavian Hendra Priyatno; Siti Halimah; Aulia Atikah (LPPM Politeknik Piksi Ganesha, 2026)
The Barito Kuala Regency History Teachers' Conference is a professional forum for Senior High School History teachers teaching in the Barito Kuala Regency. Based on data from the Barito Kuala Central Statistics Agency in 2024, Barito Kuala Regency administratively consists of 17 sub-districts with a total of 16 public senior high schools spread across almost every sub-district. This History Teachers' Conference has 29 members from 19 Senior High Schools in Barito Kuala Regency. Based on the situation analysis, there are several problems faced by partners, namely that Barito Kuala Regency History High School teachers still have difficulty designing, integrating, and evaluating digital-based formative assessments in history learning. Regarding this problem, the solution offered by the Community Service team includes conducting training on designing and creating educaplay-based formative assessments for Senior High School History teachers in Barito Kuala Regency. The output of this solution is a teaching module, a tutorial on creating educaplay-based formative assessments, and educaplay-based formative assessment products.